2011
DOI: 10.1002/qua.23131
|View full text |Cite
|
Sign up to set email alerts
|

Energetics during proton transfer process in hydrated zündel ion complex

Abstract: Zü ndel ion (H 5 O þ2 ) is one of the two important structures formed during the proton transfer process in aqueous system. This work reports microsolvation of Zü ndel ion using density functional theory based B3LYP method with aug-cc-pVTZ basis set. Interaction of Zü ndel ion with four water molecules in its first solvation shell is studied using many-body analysis approach. A change in many-body energies and their contribution to the binding energy of a complex during the proton transfer process from donor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 97 publications
1
2
0
Order By: Relevance
“…We obtained the binding energy, which is defined as the energy difference between the optimized dimer and two optimized monomers, of 19.7 kJ/mol which is in good agreement with literature value [30][31][32][33]. In addition, B3LYP was used extensively in previous studies of proton transfer in water environment [34][35][36]. Therefore, the choice of this method seems reasonable for the balance between computing cost and accuracy.…”
Section: Methodssupporting
confidence: 82%
“…We obtained the binding energy, which is defined as the energy difference between the optimized dimer and two optimized monomers, of 19.7 kJ/mol which is in good agreement with literature value [30][31][32][33]. In addition, B3LYP was used extensively in previous studies of proton transfer in water environment [34][35][36]. Therefore, the choice of this method seems reasonable for the balance between computing cost and accuracy.…”
Section: Methodssupporting
confidence: 82%
“…In this study, we will particularly consider electrochemical interfaces between Pt(111) and a water film which additionally contains ions such as hydronium and hydroxyl ions [34][35][36][37][38][39][40][41]. By performing AIMD simulations we will elucidate the structure of the electric double layer and derive the corresponding electrode potential.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that for systems whose MBEs converge quickly knowledge about molecular clusters can be systematically extended to bulk systems. Many studies have been reported in the literature investigating OH – (H 2 O) n and H 3 O + (H 2 O) n clusters using both theoretical and experimental ,, approaches. However, a rather small fraction of the theoretical work investigated many-body effects in these clusters. ,,,,,, As a first step toward a quantitative assessment of many-body effects of water self-ions in aqueous systems, we report here an analysis of OH – –water interactions in low-energy isomers of OH – (H 2 O) n clusters, with n ≤ 5.…”
Section: Introductionmentioning
confidence: 99%